PENGEMBANGAN APLIKASI PEMASARAN PRODUK STROBERI BERBASIS WEB UNTUK MENINGKATKAN PENJUALAN PADA KUBE HISHAN STRAWBERY - Yusli Yenni; Januardi Nasir; Liza Yuliana (PUAN INDONESIA, 2026)
This Community Service activity aims to support the digital transformation of SMEs, specifically KUBE Hishan Strawberry, which cultivates and sells strawberries and their processed products. The main challenges faced by partners include limited online promotion and sales, low digital technology literacy, and the lack of an online platform to expand market reach. As a solution, the team developed a web-based marketing application equipped with business profiles, product catalogs, online ordering, and stock management features, using a participatory approach to empower partners to manage their business independently. Furthermore, marketing and financial management strategies were socialized to enhance business competitiveness. The activity also included Microsoft Office training to support administration and financial record-keeping, as well as training on creating and managing social media platforms for digital promotion. Through the integration of the website and social media, KUBE Hishan Strawberry was able to expand its market reach, improve business efficiency, and build a stronger brand image.